Pattern of human bites of the oro-facial region and the indigenous mode of resolution of the resultant conflict: University of Benin Teaching Hospital experience. (Nigerian Dental Journal, 2007)
Human bite, especially involving the oro-facial region with the attendant aesthetic damage and psychological morbidity, would ordinarily attract legal action. The objective of this report is to present the pattern of human bite of the oro-facial region observed in patient victims at the University of Benin Teaching Hospital and to highlight the contribution of the indigenous mode of resolution of the resultant conflict. In a three year prospective study (2000 - 2003), six cases of oro-facial assault presented. The lower lips was involved in five of the six cases, the upper lip in one case while the nose was involved in one of those involving the lower lip. In all the six cases, there was indigenous social support and no legal action. It is concluded that the traditional support of this concept led to the early peaceful resolution of the conflicts in this community
Keywords: Human bite; Oro-facial region